2021
DOI: 10.1002/celc.202100091
|View full text |Cite
|
Sign up to set email alerts
|

3,3‐Diethylene Di‐Sulfite (DES) as a High‐Voltage Electrolyte Additive for 4.5 V LiNi0.8Co0.1Mn0.1O2/Graphite Batteries with Enhanced Performances

Abstract: A functional electrolyte containing 3,3‐diethylene di‐sulfite (DES) additive is developed to improve the performances of LiNi0.8Co0.1Mn0.1O2 (NCM811)/graphite batteries, especially at high charging cut‐off voltage of 4.50 V. It is indicated that under the conventional conditions of 25 °C and 1 C after 300 cycles in the voltage range of 2.75–4.30 V, the batteries with 0.25 % DES can increase the maximum capacity retention from 66.61 % to 77.25 % initial discharge capacity compared with the batteries without DES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Two approximate semicircles were observed in the EIS spectra after activation and cycling. The semicircle diameter in the high frequency region usually represents the interface impedance (Rsei), and the semicircle diameter in the medium frequency region usually reflects the electrochemical reaction impedance (Rct) [9,30–34] . In the ultra‐high frequency (UHF) part, the focus of impedance spectrum and coordinate axis is ohmic impedance (Rs).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two approximate semicircles were observed in the EIS spectra after activation and cycling. The semicircle diameter in the high frequency region usually represents the interface impedance (Rsei), and the semicircle diameter in the medium frequency region usually reflects the electrochemical reaction impedance (Rct) [9,30–34] . In the ultra‐high frequency (UHF) part, the focus of impedance spectrum and coordinate axis is ohmic impedance (Rs).…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that a pair of strong peaks at about −75 ppm belong to PF 6 − in lithium salt LiPF 6 . A pair of peaks at about −85 ppm can be attributed to PO 2 F 2 − , which is one of the decomposition products of the reaction between LiPF 6 and H 2 O, while the other product HF, which has a negative effect on the cycle performance of the battery, is located at approximately −190 ppm [9] . The peak intensity of PO 2 F 2 − at about −85 ppm in the electrolyte containing IMA additive is lower than that in the blank electrolyte, which indicates that IMA can inhibit the reaction between LiPF 6 and H 2 O, thus reducing the production of HF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…XPS is presented in Figure 5, the peaks at 284.7, 286.1, 288.8 and 290.0 eV belong to CÀ C, CÀ O, C=O and CÀ F bonds in the C 1s spectra, respectively. [25] The CÀ O and C=O bonds can be attributed to carbonate solvent decomposition, and the formation of CÀ C and CÀ F bonds is related to super P and PVDF (polyvinylidene fluoride). [32] Comparison of the C 1s spectra of the baseline and the electrolyte with PCS shows that the strength of CÀ O and C=O bonds is reduced after the addition of PCS.…”
Section: Surface Morphology and Composition Analysis Of Electrodesmentioning
confidence: 99%
“…[18][19][20][21] With the increase of research on electrolyte additives, it has been found that additives containing S=O bonds often have surprising effects. [22][23][24][25][26] Huang et al [27] reported that after adding methyl phenyl sulfone (MPS) to the base electrolyte, the CEI formation on the surface of LNMO (LiNi 0.5 Mn 1.5 O 4 ) had a higher ionic-conductivity than that in the baseline electrolyte, thus improving the cycle and rate capability of LNMO/Li cells at 4.9 V cut-off voltage. Lu et al [28] demonstrated that phenyl 4fluorobenzene sulfonate (PFBS) can improve the cycling stability of LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811)/graphite pouch-cell at 45 °C, because the S-containing SEI/CEI produced by PFBS improves the thermal stabilization of the electrode/electrolyte interface.…”
Section: Introductionmentioning
confidence: 99%